Obtaining the principles of economic reform from the economic life of the Holy Prophet - Dr. Tahir Siddique; Dr.Muhammad Ahmad Zuberi; Dr. Muhammad Hammad (Al-Qanṭara, 2025)
This study explores the economic principles and reforms derived from the economic life of the Prophet Muhammad (peace be upon him) and examines their application to modern economic systems. The economic practices of the Prophet (peace be upon him) are not only reflective of Islamic teachings but also offer comprehensive guidelines for achieving social justice, economic equity, and sustainable development. Drawing from the Prophet’s personal conduct, governance, and interactions with the community, this study identifies key principles that can inform contemporary economic reforms. The analysis begins by exploring the Prophet’s emphasis on ethical commerce, where honesty, transparency, and fairness were paramount. The prohibition of riba (interest) is analyzed as part of the Prophet’s economic reforms, promoting the circulation of wealth, and discouraging the exploitation of the financially vulnerable. The concept of zakat (charity) is examined as a powerful mechanism for redistributing wealth, alleviating poverty, and fostering a sense of collective responsibility in the economy. Furthermore, the study highlights the Prophet’s encouragement of fair wages, honest labor, and the promotion of mutual benefit in economic transactions. Key principles such as social justice, equitable distribution of resources, and ethical entrepreneurship are explored in depth, drawing attention to how the Prophet’s model balanced the interests of individuals and communities. The Prophet’s leadership, which emphasized welfare policies such as public spending on infrastructure, social safety nets, and protection of the vulnerable, is a key part of the analysis. These policies ensured that wealth was not concentrated in the hands of a few but was distributed in a way that promoted overall social well-being.